1994
DOI: 10.1111/j.1365-2125.1994.tb04333.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of non‐invasive measurement and of short‐term variability of blood pressure and heart rate in healthy volunteers.

Abstract: 1 Spectral analyses of blood pressure and heart rate oscillations are increasingly used to assess the influences of diseases and drugs on the autonomic nervous system. Such influences can only be interpreted in view of the spontaneous variability of these oscillations. We therefore studied the reproducibility of power spectral analyses of blood pressure and heart rate fluctuations measured by a non-invasive finger plethysmographic method in 24 healthy volunteers. 2 Intra-observer reproducibility was assessed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
2
9
0
1
Order By: Relevance
“…Specifically, studies have shown frequency domain measures of BPV to be highly reproducible in healthy individuals [6,8], but as intraclass correlations were not used in those investigations direct comparisons to the present study are not possible.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Specifically, studies have shown frequency domain measures of BPV to be highly reproducible in healthy individuals [6,8], but as intraclass correlations were not used in those investigations direct comparisons to the present study are not possible.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, measures of HRV and BPV are attractive means to evaluate changes in cardiovascular health and fitness in response to various interventions including exercise training. The true efficacy of HRV and BPV measures in this respect, however, hinge largely on their day-to-day reproducibility, and as such several investigations have been published in this area in both healthy individuals [8,25,31], and those with cardiovascular disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other groups, including normal subjects [9], subjects with Type I diabetes [10], chronic angina sufferers [11] and subjects with congestive heart failure [12], have suggested that low-frequency HRV is a reproducible measurement. Those studies dealt largely with measurements from 24 h tapes, which were repeated only once and at varying time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Indices of autonomic circulatory control have been shown by our group and numerous other investigators to be quite stable over time and between study days at baseline conditions in a variety of study populations. 19,[23][24][25] For this reason a time control group was not justified, and the changes in measurements over time can be assumed to be due primarily to drug effects at the different infusion rates. In addition, although the investigators administering the protocol were unblinded and could have been biased in the assignment of sedation scores, the drug infusion scheme was designed to target specific plasma concentrations, rather than titrating to sedation score.…”
Section: Methodsmentioning
confidence: 99%